A chemo-mechanical snapshot of in-situ conversion of kerogen to petroleum. (15th March 2020) - Abarghani, Arash; Ostadhassan, Mehdi; Hackley, Paul C.; Pomerantz, Andrew E.; Nejati, Siamak
Abstract: Organic matter (OM) from various biogenic origins converts to solid bitumen in-situ when it undergoes thermal maturation. It is well documented that during this process, the ratios of both hydrogen and oxygen to carbon will decrease, resulting in an increase in OM aromaticity and molecular chemo-mechanical homogeneity. Although there have been extensive efforts to reveal molecular alteration occurring to OM during conversion, in-situ and continuous observation of such alterations on naturally occurring samples is missing. Therefore, evaluation of previous results cannot be made independent from natural sample variability. In this study, we identified OM particles ( Tasmanites ) that are evolving in-situ into solid bitumen in the Bakken Formation. This in-situ bituminization allows examination of a continuous transformation in OM molecular structure at micron-scale using AFM based IR spectroscopy applied at the transition/interface zone. Moreover, contact mode in the AFM was employed to reveal and relate changes in mechanical properties at a similar scale of measurement. Understanding these chemical and mechanical alterations is important to understand shale reservoir properties and better explain hydrocarbon generation, expulsion, and migration processes at the microscale.